The mastering of the composition of the thematic drawing with a plot in elementary forms - Tribandienė, D. (Psichologija, 1977)
Children’s drawings reflect theor knowledge and their attitude to the world. Together with other complex elements in these drawings there is a problem of composition to discuss. The problem of composition is of the greatest importance in any drawing regardless of its genre, theme and character, so in the process of drawing pupils must develop their visual compositional way of thinking, they must be able to create and summarize the phenomena of the reality they observe by means of art forms.